2020
DOI: 10.3892/etm.2020.8990
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography maximum amplitude predicts short‑term mortality in patients with hepatitis B virus‑related acute‑on‑chronic liver failure

Abstract: Patients with hepatitis B virus (HBV)-related acute-on-chronic liver failure (ACLF) exhibit complex hemostatic defects. Thromboelastography (TEG) can be used to reveal global hemostasis in patients with liver disease; however, little is known about the association between TEG and the outcome of patients with HBV-related ACLF. The present study aimed to investigate the value of TEG for predicting 90 day mortality in patients with HBV-related ACLF. A total of 51 patients with HBV-related ACLF, 26 patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, protein C activity (<30%), but not clot lysis, is an independent predictor of mortality in patients with ACLF after adjusting for age, gender and baseline MELD. 55 INR (AUROC = 0.865, p = 0.001) seems to have a higher predictive value of mortality than MA (AUROC = 0.771, p = 0.001) in ACLF 61 . Additionally, R and α are not associated with the mortality or hospice in patients with cirrhosis after adjusting for MELD score or presence of ACLF 13 .…”
Section: Teg Profile and In Liver Dise A Se Smentioning
confidence: 90%
See 2 more Smart Citations
“…However, protein C activity (<30%), but not clot lysis, is an independent predictor of mortality in patients with ACLF after adjusting for age, gender and baseline MELD. 55 INR (AUROC = 0.865, p = 0.001) seems to have a higher predictive value of mortality than MA (AUROC = 0.771, p = 0.001) in ACLF 61 . Additionally, R and α are not associated with the mortality or hospice in patients with cirrhosis after adjusting for MELD score or presence of ACLF 13 .…”
Section: Teg Profile and In Liver Dise A Se Smentioning
confidence: 90%
“…59 There is a significant difference in haemostatic status indicated by TEG profile and CCTs between ACLF patients who survived and died. 18,60,61 TEG parameters, mainly including K, α, MA, clot lysis and coagulation index, 55,61 can predict the short-term outcome of patients with ACLF. However, protein C activity (<30%), but not clot lysis, is an independent predictor of mortality in patients with ACLF after adjusting for age, gender and baseline MELD.…”
Section: Teg Profile and In Liver Dise A Se Smentioning
confidence: 99%
See 1 more Smart Citation
“…At baseline, the PELD (28 [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] versus 31 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]; P = 0.28), MELD (25 [24][25][26][27][28][29][30] versus 32 [27][28][29][30][31][32]; P = 0.93), CTP (12 Vinayagamoorthy et al [11][12] versus 12 [12][13]; P = 0.6), and pCLIF-SOFA score (7 [6-8] versus 7 [6][7]…”
Section: Severity Of Liver Dysfunction and Tegmentioning
confidence: 99%
“…In addition, among the enrolled ACLF patients, those with a hypocoagulation TEG profile had a significantly higher risk of bleeding [hazard ratio (HR) 2.1; CI: 1.6-4.9; P = 0.050] and short-term mortality (HR 1.9; CI: 1.3-7.9; P = 0.043). A more recent Chinese report[ 45 ] compared 51 hepatitis B virus-related cases of ACLF with healthy controls and patients with fully compensated chronic hepatitis B. They found that the coagulation dynamics were significantly altered in ACLF, with higher R and K times and lower α angles and MAs, corresponding to a marked hypocoagulable state.…”
Section: Hypercoagulability Thrombosis and Vet In Liver Cirrhosismentioning
confidence: 99%